A Lactococcus lactis BFE920 feed vaccine expressing a fusion protein composed of the OmpA and FlgD antigens from Edwardsiella tarda was significantly better at protecting olive flounder (Paralichthys olivaceus) from edwardsiellosis than single antigen vaccines. Issue 68 (September 2017) - Beck, Bo Ram; Lee, Soon Ho; Kim, Daniel; Park, Ji Hye; Lee, Hyun Kyung; Kwon, San-Sung; Lee, Kwan Hee; Lee, Jae Il; Song, Seong Kyu
Abstract: Edwardsiellosis is a major fish disease that causes a significant economic damage in the aquaculture industry. Here, we assessed vaccine efficacy after feeding oral vaccines to olive flounder ( Paralichthys olivaceus ), either L. lactis BFE920 expressing Edwardsiella tarda outer membrane protein A (OmpA), flagellar hook protein D (FlgD), or a fusion antigen of the two. Feed vaccination was done twice with a one-week interval. Fish were fed regular feed adsorbed with the vaccines. Feed vaccination was given over the course of one week to maximize the interaction between the feed vaccines and the fish intestine. Flounder fed the vaccine containing the fusion antigen had significantly elevated levels T cell genes ( CD4-1, CD4-2, and CD8α ), type 1 helper T cell (Th1) subset indicator genes ( T-bet and IFN-γ ), and antigen-specific antibodies compared to the groups fed the single antigen-expressing vaccines. Furthermore, the superiority of the fusion vaccine was also observed in survival rates when fish were challenged with E. tarda : OmpA-FlgD-expressing vaccine (82.5% survival); FlgD-vaccine (55.0%); OmpA-vaccine (50%); WT L. lactis BFE920 (37.5%); Ctrl (10%). In addition, vaccine-fed fish exhibited increased weight gain (∼20%) and a decreased feed conversion ratio (∼20%) during the four week vaccination period. Flounder fed the FlgD-expressing vaccine, either the single or the fusion form, had significantly increased expression of TLR5M, IL-1β, and IL-12p40, suggesting that the FlgD may be a ligand of olive flounder TLR5M receptor or closely related to the TLR5M pathway. In conclusion, the present study demonstrated that olive flounder fed L. lactis BFE920 expressing a fusion antigen composed of E. tarda OmpA and FlgD showed a strong protective effect against edwardsiellosis indicating this may be developed as an E. tarda feed vaccine. Highlights: The fusion antigen composed of E. tarda OmpA and FlgD is developed. Feeding the fusion antigen expressing L. lactis effectively protects flounder. The TLR5M expression level in vaccinated fish was increased by FlgD subunit. The fusion vaccine showed enhanced vaccine efficacy compared to single antigens.